Imperforate Hymen: A Rare Cause of Abdominopelvic Mass in an Infant - Dixit Thapa, Baburam; Regmi, Mohan Chandra (Journal of Nepal Health Research Council, 2021)
Symptomatic imperforate hymen is very rare in infants. Here we report a neonate who presented with imperforate hymen with abdominal distension, fever and loose stool. Imaging study showed large thick walled cystic lesion extending from pelvis to abdomen upto epigastric region with bilateral mild hydroureteronephrosis and lower part in between urinary bladder and rectum suggesting hydrometrocolpos. There was spontaneous rupture leading to flow of collection. It leads to spontaneous resolution of the mass which was confirmed with pelvic ultrasound and computed tomography.Keywords: Hydrometrocolpos; hydroureteronephrosis; imperforate hymen